2020
DOI: 10.1002/cncr.32659
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation for blood cancers in the era of precision medicine and immunotherapy

Abstract: Hematopoietic stem cell transplantation (HCT) has been an integral component in the treatment of many hematologic malignancies. Since the development of HCT nearly 50 years ago, the role of this modality has evolved as newer treatment approaches have been developed and integrated into the standard of care. In the last decade, novel and highly active targeted therapies and immunotherapies have been approved for many hematologic malignancies, raising the question of whether HCT continues to retain its prominent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 157 publications
(175 reference statements)
0
24
0
1
Order By: Relevance
“…Hematological diseases are a series of heterogeneous diseases associated with abnormal blood changes that originate from the hematopoietic system or affect the hematopoietic system. Autologous or allogeneic HSCT are critical therapy tools to treat malignant and non-malignant hematological diseases ( Bair et al, 2020 ; Mallhi et al, 2020 ). In order to completely clear immune system of recipient before HSCT, it is necessary to use high-dose chemotherapy drugs for pretreatment.…”
Section: Application Of Uc-mscs In Hematologic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematological diseases are a series of heterogeneous diseases associated with abnormal blood changes that originate from the hematopoietic system or affect the hematopoietic system. Autologous or allogeneic HSCT are critical therapy tools to treat malignant and non-malignant hematological diseases ( Bair et al, 2020 ; Mallhi et al, 2020 ). In order to completely clear immune system of recipient before HSCT, it is necessary to use high-dose chemotherapy drugs for pretreatment.…”
Section: Application Of Uc-mscs In Hematologic Diseasesmentioning
confidence: 99%
“…In order to completely clear immune system of recipient before HSCT, it is necessary to use high-dose chemotherapy drugs for pretreatment. However, the negative effects of bone marrow hematopoietic microenvironment damage and delayed immune reconstitution may lead to poor stem cell engraftment, and increase the rate of postoperative infection and recurrence ( Bair et al, 2020 ; Mallhi et al, 2020 ). A series of animal and clinical trials showed that HSCT or cord blood transplantation (CBT) combined with infusion of UC-MSCs is able to promote hematopoietic engraftment and reduce the occurrence GVHD ( Liu et al, 2020c ; Yang et al, 2020 ).…”
Section: Application Of Uc-mscs In Hematologic Diseasesmentioning
confidence: 99%
“…Dans le traitement des leucémies aiguës myéloblastique, elle est indiquée chez les patients en première rémission, pour les leucémies à bas risque et avec une maladie résiduelle indétectable [52] . L’allogreffe reste le traitement de référence pour les leucémies aiguës myéloblastiques de l’adulte en première rémission chez ceux qui ont un risque de récidive de 35 à 40 %, en cas d’anomalies cytogénétiques péjoratives ou de myélodysplasie préexistante [53] , [54] . Elle est aussi indiquée dans les leucémies aiguës lymphoblastiques de l’adulte avec anomalies cytogénétiques défavorables, en cas de phénotype pré-B et chez les patients avec un taux de leucocytes élevés au diagnostic.…”
Section: Cellules Souches Hématopoïétiques Et Cellules Car-tunclassified
“…In human medicine, allogeneic hematopoietic cell transplantation (HCT) is a critical therapy for haematological malignancies, such as lymphoma or leukemia (Bair et al., 2020; Baron & Storb, 2006; Copelan et al., 2019). In the veterinary field, there are few reports on allogeneic HCT for dogs (Lupu et al., 2006; Suter et al., 2015).…”
Section: Introductionmentioning
confidence: 99%